Pengaruh Faktor Internal Dan Faktor Eksternal Terhadap Kinerja Pedagang Kaki Lima Melalui Orientasi Kewirausahaan di Tawangmangu Karanganyar Jawa Tengah - Nuryati .; Endang Sri Suwarni (Universitas Muhammadiyah Ponorogo, 2017)
The aim of research to examine the influence of internal factors and external factors on the performance of vendors through entrepreneurial orientation in Tawangmangu Karanganyar regency, Central Java. This study took a sample of street vendors in Karanganyar, Central Java Tawangmangu some 150 street vendors. This study use path analysis. Hypothesis test results show that internal factors and external factors influence the entrepreneurial orientation and performance of vendors Entrepreneurial orientation does not affect the performance of street vendors. The variable external factors more effectively the performance of vendors without going through orientansi entrepreneurship.